Pemodelan Spasial Perubahan Penggunaan Lahan di Taman Nasional Gunung Halimun Salak dan Daerah Penyangganya - Iwan Kurniawan; Baba Barus; Andrea Emma Pravitasari (P4W LPPM IPB, 2017)
Land use activities in Gunung Halimun Salak National Park (GHSNP) that does not comply with the zoning plan of GHSNP cause degradation, deforestation and decreasing GHSNP size, while land use activities intensively in the surrounding of GHSNP (buffer area) that does not comply with the spatial allocation plan may alter landscape configuration that influence ecological processes and biodiversity within national park. Predicting land use and land cover (LULC) change patterns in the future provides important information for identifying areas that vulnerable to changes. Multi-temporal remote sensing data was used to identify LULC, a multi-layer perceptron neural network with a Markov chain model (MLPNN-M) was used to predict LULC in 2025 and to analyze LULC trend, Overlaying analysis was used to analyze the consistency between LULC and spatial allocation regulation in 2025. The results show that LULC in GHSNP and its buffer area consist of prmary forests, secondary forests, mixture crops, plantations, settlements, agriculture, shrubs, and water. The primary forests, secondary forests, mixture crops, and agriculture were predicted to decrease while settlements, plantations and shrubs were predicted to increase. Land conversion trends into secondary forests, plantations, agriculture and shrubs that begin to show centralized patterns within and the boundaries of GHSNP need to be anticipated. In 2025, inconsistency between land use and GHSNP zonation is the existence of mixture crops, plantations, settlements and agriculture outside the special zone whereas inconsistency between land use and spatial allocation regulation is existence of plantations and agriculture in conservation forest, protection forest and production forest.